ANALISIS STRUKTURALISME NASKAH DRAMA TARLING “DOKTER PALSU” KARYA HJ. DARIYAH - Saroni (Universitas Wiralodra, 2019)
Tarling is a musical intellectual that contributes to the uplift of Indramayu's cultural arts. According to Hidayatulla (2005) the art of tarling still exists and is developing, but its existence does not receive much attention from the community, especially the younger generation. The cultural development is emphasized by Maknum (2004: 81) the process of art development is influenced by several factors namely scientific, environmental, and time factors. All three take place interactively. As a cultural product, art in its development will be subject to the main laws that govern human development. The diversity of Tarling music that continues to change and develop in the wider community, is feared to reduce the function of identity, as well as undergoing changes in shape which ultimately is not impossible that will farther and lose its original form. The main objective of this research is an effort in the inheritance and preservation of Indramayu culture by realizing the design of the staging of the Tarling drama script